Pengaruh Karakteristik Demografi Terhadap Tingkat Kesejahteraan Masyarakat Di Indonesia - Nuraini Kabaderan; Syarwani Canon; Boby Rantow Payu (STIE Jambatan Bulan, 2024)
The research aims to find out how demograpich characteristics influence the level of social welfare in Indonesia. The research method used is a quantitative method with secondary data sourced from the Central Statistics Agency (BPS). The data analysis technique used is multiple linier regression analysis technique. In this study, the test result found that (1) Total Fertility Rate/TFR did not have a significant effect on the level of social welfare in Indonesia because the value of Prob. 0,1394 > 0,05 (2) Population/KP density has a significant effect on the level of social welfare in Indonesia because the value of Prob. 0,0000 < 0,05 (3) Dependency Ratio/DR does not have a significant effect on the level of social welfare in Indonesia because the value of Prob. 0,0063 > 0,05 (4) Sex Ratio/SR does not have a significant on the level of social welfare in Indonesia because the value of Prob. 0,6761 > 0,05.